On the security issues of NFC enabled mobile phones. (7th December 2010) - Francis, Lishoy; Hancke, Gerhard; Mayes, Keith; Markantonakis, Konstantinos
In this paper, we investigate the possibility that a Near Field Communication (NFC) enabled mobile phone, with an embedded secure element (SE), could be used as a mobile token cloning and skimming platform. We show how an attacker could use an NFC mobile phone as such an attack platform by exploiting the existing security controls of the embedded SE and the available contactless APIs. To illustrate the feasibility of these actions, we also show how to practically skim and emulate certain tokens typically used in payment and access control applications with a NFC mobile phone. We also discuss how to capture and analyse legitimate transaction information from contactless systems. Although such attacks can also be implemented on other contactless platforms, such as custom-built card emulators and modified readers, the NFC enabled mobile phone has a legitimate form factor, which would be accepted by merchants and arouse less suspicion in public. Finally, we propose several security countermeasures for NFC phones that could prevent such misuse.